(3TQM GddHGH aj Yde GdEYQGHs - (3bWH GdOjf eMeO Hf eSYhO Hf eMehO Hf CHj GdaJM GdZGdj GdTbGQ GdSjQGajs; (3eMeO Hf eMeO Hf CMeO, JGL GdOjf GdCSaQGjjfj,J (B684 (3g` s ((3NhGQRe s)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG Edi eYQaI EYLGR GdbQBf cJGH GddHGH aj GdfMh cJGH dG jNai ebOGQg s
(3BNQgG (B:s
(3hGdUaI bO Jchf GSe aGYd EPG cGf GdehUha fcQI hEP bO hajfG HeG hYOfG s
(3GddHGH ai Yde GdEYQGH GdeSei dH GdGdHGH ai Yde GdEYQGHs
(3eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs